Food insecurity and its determinants in pastoralist and agrarian communities in South Omo Zone, Southern Ethiopia: a community-based cross-sectional study - Gujo, Mintesinot Melka; Modiba, Lebitsi Maud (Frontiers in Public Health, 2024)
Background Despite the implementation of different interventions, food insecurity remains a major public health issue in rural areas of Ethiopia. However, there has been limited evidence regarding food insecurity and responsible factors in rural areas of Ethiopia, particularly in South Omo, Ethiopia. Hence, this study aimed to assess food insecurity and determinants in agrarian and pastoralist communities of South Omo Zone, Southern Ethiopia. Methods A cross-sectional study was done among 605 randomly selected households in Benatsemay and South Ari districts from February 1 to 28, 2023. A standardized and validated Household Food Insecurity Access Scale (HFIAS) was used to measure food insecurity status. Data were entered using Epi-Info 7.1 and then transferred to SPSS V25 for analysis. To identify associated factors, a binary logistic regression model was employed. The strength of association was evaluated considering the adjusted odds ratio (AOR) and a 95% confidence interval (CI). A statistical significance was stated at p-value <0.05. Result A total of 597 participants were involved in the study with a response rate of 98.7%. The overall prevalence of food insecurity using HFIAS was 42.2% (95%CI: 38.2, 46.3%), among which mild, moderate, and severe food insecurity accounted for 17.4, 16.6, and 8.2%, respectively. Of pastoralists, 114 (47.1%) were food insecure whereas 138 (38.9%) were food insecure in the agrarian. Food insecurity was affected by household head sex (AOR = 1.73, 95%CI: 1.14, 2.62), high dependency ratio (AOR = 2.53, 95%CI: 1.53, 4.20), no formal maternal education (AOR = 2.11, 95%CI: 1.07, 4.18), productive safety net program (AOR = 2.00, 95%CI: 1.16, 3.46) and land ownership (AOR = 1.80, 95% CI: 1.19, 2.72). Conclusion Food insecurity was a significant problem in the study areas. Thus, it is crucial to improve female education, advance agricultural technologies, advocate family planning, and broaden productive safety net programs.